Pertanggungjawaban hukum Anak Usia di Bawah 14 Tahun dalam Sistem Peradilan Pidana Anak Indonesia - Khana Amalia Rizki; Hafrida Hafrida; Elizabeth Siregar (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
The regulation of accountability and sanctions for children aged 12–14 years in the juvenile criminal justice system in Indonesia raises normative issues, particularly regarding the unclear position of children as subjects of legal accountability who cannot be punished as stipulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study aims to analyze the regulation of sanctions against children aged 12–14 years and formulate a direction for fair child accountability regulations. The research method used is normative juridical with a legislative, conceptual, and case approach. The results of the study indicate that there is ambiguity in the norms of the SPPA Law, which requires reformulation through a tiered accountability model and harmonization with the National Criminal Code to ensure child protection, legal certainty, and proportional justice.